Individual differences in chemotherapy-induced anticipatory nausea - Rodríguez, Marcial (Frontiers in Psychology, 2013)
Anticipatory Nausea (AN) is a severe side effect of chemotherapy that can lead cancer patients to discontinue their treatment. This kind of nausea is usually elicited by the re-exposure of the patients to the clinical context they need to attend to be treated. There has been considerable agreement that AN represents a paradigmatic example of Pavlovian conditioning, and within this framework, several behavioral interventions have been proposed in order to prevent this psychopathology. However, some studies have questioned the validity of the Pavlovian approach, suggesting that CS-US associations are neither necessary nor sufficient for AN to occur. The data and the alternative theories behind such criticisms are discussed. Additionally, it is suggested that animal models of AN could be enriched by taking into account rats’ individual differences.